1997
DOI: 10.1089/lap.1997.7.1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Appendectomy: A Viable Alternative Approach

Abstract: Laparoscopic appendectomy (LA) is relatively a new technique and requires comparison to open appendectomy (OA) to determine the more favorable approach in the surgical management of acute appendicitis. We designed this study to compare the course and postoperative complications between LA and OA. We reviewed the charts of both groups of patients and followed their course in the hospital. Seventy-seven patients who underwent LA with one conversion to the open technique (1.3%) were compared to 84 patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…This may be due to a single small incision of 10 mm and muscle spitting technique which were used for trocar placement. Postoperative hospital stay was 1.4 ± 1.2 days, which was lower than that associated with conventional LA or open appendectomy, as has been shown in other studies [10,11]. There was no remarkable complication.…”
Section: Methodssupporting
confidence: 56%
“…This may be due to a single small incision of 10 mm and muscle spitting technique which were used for trocar placement. Postoperative hospital stay was 1.4 ± 1.2 days, which was lower than that associated with conventional LA or open appendectomy, as has been shown in other studies [10,11]. There was no remarkable complication.…”
Section: Methodssupporting
confidence: 56%
“…In a nonrandomized trial of 122 patients Schirmer et al found no significant difference in hospital stay. 16 Some recent retrospective cohort studies [17][18][19] shows a significant shorter hospital stay after LA while other shows no significant differences in hospital stay .20, 21 CONCLUSION: This study identified the value of the laparoscopic technique for appendectomy in a non-specialist center. This benefits the patients with its low morbidity, shorter hospital stay, minimal operating time and quicker recovery.…”
Section: Discussionmentioning
confidence: 78%
“…[12][13][14][15][16] Some recent retrospective cohort studies, meta-analysis studies and other retrospective investigation have reported lesser hospital stay. [11][12][13][17][18][19] There have been many other similar studies, who have reported no significant difference between laparoscopic and open surgeries. [20][21][22][23][24][25] Present study showed a significant reduction in the number of hospital days, with the mean in laparoscopic group being 2.2 days and among the open group the mean was 3.1 days.…”
Section: Discussionmentioning
confidence: 99%